2013
DOI: 10.1111/ijn.12014
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for success for first semester, second‐degree Bachelor of Science in Nursing students

Abstract: Second-degree Bachelor of Science in Nursing (BSN) programmes have grown rapidly in the past 5 years to respond to the nursing shortage in many countries. The purposes of this study are to describe the relationships among age, prerequisite grades, previous degree grade point averages (GPAs), admissions test scores and first semester test scores, and to investigate the most influential predictor for success in the first semester in the nursing program. Pre-existing data from academic records were used. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Similarly, the ATI TEAS ® pre‐admission standardized assessment scores have shown a high correlation with successful students (ATI, ; Cherkis & Rosciano, ; Horton, Pollek, & Hardie, ; Wolkowitz & Kelley, ), while pre‐admission interview and other student input criteria were not strong indicators of success (McNelis et al, ). Studies have shown that students who are older and have a higher re‐requisite GPA have a greater likelihood of successful completion of a nursing programme (Kowitlawakul, Brenkus, & Dugan, ; Pryjmachuk, Easton, & Littlewood, ). Studies of multiple combinations of variables have not isolated those traits that consistently identify the students most likely to be successful, indicating the need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the ATI TEAS ® pre‐admission standardized assessment scores have shown a high correlation with successful students (ATI, ; Cherkis & Rosciano, ; Horton, Pollek, & Hardie, ; Wolkowitz & Kelley, ), while pre‐admission interview and other student input criteria were not strong indicators of success (McNelis et al, ). Studies have shown that students who are older and have a higher re‐requisite GPA have a greater likelihood of successful completion of a nursing programme (Kowitlawakul, Brenkus, & Dugan, ; Pryjmachuk, Easton, & Littlewood, ). Studies of multiple combinations of variables have not isolated those traits that consistently identify the students most likely to be successful, indicating the need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Other intrinsic factors were the grade of entrance test and admission criteria (Ortega, 2013). The admission test become a significant factor to become one of predictor to contrive the assessment, designing learning and help the students in a learning process in their first year (Kowitlawakul, 2013). Age, background the culture, education background, academic accomplishments, thinking style, learning style, personality style and coping strategic style were also regarded as an intrinsic factors (Abdilah, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another perspective in contributing in lower grade results of this competency test because of some mistaken in registration process, miscommunication and the absence of specific strategies from the managers of three years diploma degree in nursing to create graduates with high capability so that the competency test will successfully attained. External factors of readiness and strategies of management were factors that need to be explored more seriously in attaining the best results of competency test (Koestler (2017), Lavin & Rosario (2017), Kowitlawakul (2013) & Simon (2013. What are the factors, best strategies and readiness of the three years nursing diploma program managers in preparing the graduate students in conjunction to produce successful try out national competency examination and successful national competency test?…”
Section: Introductionmentioning
confidence: 99%
“…As with mathematical self-efficacy, GPA was a notable predictor for high performance in mathematics testing in this study. A growing body of evidence supports the link between previous high GPA and high academic performance (Kowitlawakul, Brenkus, & Dugan, 2013;Söderlind & Geschwind, 2017;Wambuguh, Eckfield, & Hofwegen, 2016); however, this is not specific to mathematical achievement. Hence, our study further underscores the importance of developing educational strategies that support under-achieving students to strengthen their self-efficacy, in order to improve their mathematical performance and competence.…”
Section: Bäckströmmentioning
confidence: 99%